2016
DOI: 10.1136/neurintsurg-2016-012319
|View full text |Cite|
|
Sign up to set email alerts
|

Optimizing endovascular stroke treatment: removing the microcatheter before clot retrieval with stent-retrievers increases aspiration flow

Abstract: The BWT technique results in improved aspiration flow rates compared with the standard deployment technique. Our clinical data show that the BWT technique is effective and safe.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 25 publications
1
35
0
Order By: Relevance
“…This has been shown experimentally to significantly increase the suction force 9. Again, we monitor the drip rate on the aspiration tubing to ensure near stasis.…”
Section: Methodsmentioning
confidence: 99%
“…This has been shown experimentally to significantly increase the suction force 9. Again, we monitor the drip rate on the aspiration tubing to ensure near stasis.…”
Section: Methodsmentioning
confidence: 99%
“…The aspiration flow (milliliters/second) was obtained by dividing the collected volume by the aspiration time. 5 Aspiration with a syringe was assessed as aspirated volume with time. For measurements through the sheath and balloon catheter, we used an ultrasonic flow meter (HT110 Bypass Flowmeter & Tubing Sensor; Transonic, Ithaca, New York), due to the high flow through these catheters.…”
Section: Methodsmentioning
confidence: 99%
“…1 In past years, the focus of neurointerventional stroke research has shifted from establishing the method to finding the optimal treatment technique. [2][3][4][5][6] Effective blood flow management during the procedure is key to safety and effectiveness. 7 Chueh et al 2 have shown that there are thousands of small clot fragments during thrombectomy that may occlude small arterioles and capillaries.…”
mentioning
confidence: 99%
“…In that scenario, suction force would only be minimally impacted by the slight reduction in transmitted vacuum pressure. Therefore, it would seem that the microcatheter does not need to be removed completely, as others have advocated with the “bare-wire thrombectomy” technique [19], but rather simply be pulled back so that the microcatheter tip is proximal to the aspiration catheter tip.…”
Section: Discussionmentioning
confidence: 99%
“…When using such a coaxial approach, the stent retriever delivery microcatheter may partially occlude the aspiration catheter and thereby potentially reduce the vacuum force. Therefore, some have recommended a “bare-wire thrombectomy” technique wherein the delivery catheter is removed prior to aspiration and thrombectomy [19]. These authors have also assessed flow rates through the aspiration catheter with and without the microcatheter in place (Poiseuille fluid dynamics), but have not assessed the static suction force in this scenario.…”
Section: Introductionmentioning
confidence: 99%